Preparation method and application of zinc negative electrode with MCM-41 protective layer
By coating the MCM-41 protective layer on the surface of the zinc metal negative electrode, the problem of poor stability of the zinc negative electrode in the aqueous electrolyte is solved, the cycle stability and electrochemical performance of the zinc ion battery are significantly improved, and dendrites are inhibited and the growth and corrosion of dendrites are inhibited. Response, extending the battery life.
Patent Information
- Application Number
- CN202411355706.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
AI Technical Summary
The zinc metal negative electrode has poor stability in aqueous electrolytes and is prone to corrosion and hydrogen evolution, resulting in dendrites growing, piercing the separator, causing battery short circuits, reducing stability and cycle life.
The MCM-41 protective layer is coated on the surface of the zinc metal negative electrode, and the MCM-41 powder is formed by heating and stirring cetyl trimethylammonium bromide, sodium hydroxide, deionized water and ethyl orthosilicate. It is mixed with polyvinylidene fluoride, scraped on the surface of the zinc negative electrode, and vacuum dried to make a zinc negative electrode with a protective layer of MCM-41.
It significantly improves the cycle stability and electrochemical performance of aqueous zinc ion batteries, inhibits dendrites' growth and corrosion reaction, extends the battery's service life and reduces internal resistance.
Smart Images

Figure CN119208502A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemical energy storage materials, and in particular to a preparation method and application of a zinc negative electrode with an MCM-41 protective layer. Background Art
[0002] With the transformation of the global energy structure, traditional fossil energy is gradually being replaced by clean energy. However, renewable energy sources such as wind and solar energy are intermittent and unstable, and large-scale energy storage equipment is needed to balance supply and demand. Lithium-ion batteries are widely used due to their high energy density and long cycle life, but their high cost, safety issues and uneven resource distribution limit their development. To address these issues, aqueous zinc-ion batteries, as an emerging energy storage technology, have attracted attention due to their low cost, high safety and environmental friendliness. Zinc resources are abundant, low in price, high in energy density and easy to process, which is conducive to its application in large-scale energy storage systems. Taking all the above conditions into consideration, aqueous zinc-ion batteries have great development prospects in energy storage systems.
[0003] However, the stability of zinc metal anode in aqueous electrolyte is poor. When zinc metal is in direct contact with water molecules in the electrolyte during the charge and discharge process, side reactions such as corrosion and hydrogen evolution will inevitably occur. These side reactions will consume zinc and active substances in the electrolyte. During the charge and discharge process, the tip effect causes uneven deposition and stripping of zinc ions, which triggers dendrite growth. When the dendrite grows to a certain extent, it will pierce the diaphragm, causing the battery to short-circuit, resulting in a sharp decrease in battery stability and cycle life. At the same time, if the dendrite falls off, "dead zinc" will be formed, resulting in battery capacity loss and increased internal resistance. Therefore, it is crucial to develop an aqueous zinc ion battery anode that can simply and efficiently improve the safety and cycle stability of aqueous zinc ion batteries. In recent years, people have adopted a variety of strategies to alleviate or inhibit the growth of dendrites and avoid side reactions, including interface modification, electrode structure modification, electrolyte optimization, etc. Among them, interface modification is considered to be an attractive method, and adding a protective layer on the surface of the zinc anode is the most prominent as a simple and effective method. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a zinc negative electrode with an MCM-41 protective layer and its application in view of the shortcomings of the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a zinc negative electrode having an MCM-41 protective layer, comprising the following steps:
[0007] 1) Hexadecyltrimethylammonium bromide, sodium hydroxide and deionized water were heated and stirred for 1.5 hours, and then ethyl orthosilicate was added and heated and stirred for 2 hours to obtain a mixed solution. The obtained mixed solution was aged in an air atmosphere for 15 hours, centrifuged and washed, and then dried and placed in a porcelain boat, and the temperature was uniformly raised to 550° C. and calcined for 4 hours, and then naturally cooled to obtain MCM-41 powder;
[0008] 2) The obtained MCM-41 powder and polyvinylidene fluoride were ground and mixed in a mass ratio of 9:1, N-methylpyrrolidone was added dropwise and magnetic stirring was performed for 4 hours to prepare a slurry, and the obtained slurry was evenly scraped on the surface of the zinc metal negative electrode with a scraper, and the zinc negative electrode with an MCM-41 protective layer was obtained after vacuum drying.
[0009] Furthermore, in the step 1), the mass ratio of hexadecyltrimethylammonium bromide, sodium hydroxide, deionized water, and ethyl orthosilicate is 1:0.15:192.31:4.81;
[0010] Furthermore, the heating and stirring temperature in step 1) is 40 to 80° C.;
[0011] Furthermore, in step 1), the aging temperature is 40 to 80° C., and the aging time is 10 to 15 hours;
[0012] Furthermore, in step 1), the drying temperature is 40-80° C. and the drying time is 48 hours;
[0013] Furthermore, in step 1), the calcination heating rate is 1-2°C / min;
[0014] Furthermore, in step 2), the vacuum drying temperature is 40 to 80° C., and the vacuum drying time is 10 to 15 hours;
[0015] The invention provides a method for preparing a zinc negative electrode with an MCM-41 protective layer. The process is simple and easy to control, the production cost is low and the efficiency is high, and the method is suitable for large-scale production. The prepared zinc negative electrode with the MCM-41 protective layer significantly improves the cycle stability and electrochemical performance of an aqueous zinc ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 XRD diagrams of the zinc negative electrode with MCM-41 protective layer prepared in the embodiment of the present invention and the unmodified bare zinc negative electrode in the comparative example;
[0017] Figure 2 The SEM images of the zinc negative electrode with the MCM-41 protective layer prepared in the embodiment of the present invention and the unmodified bare zinc negative electrode in the comparative example;
[0018] Figure 3The cycle performance diagram of the symmetrical battery assembled with the zinc negative electrode having the MCM-41 protective layer prepared in the embodiment of the present invention and the symmetrical battery assembled with the unmodified bare zinc negative electrode in the comparative example;
[0019] Figure 4 The figure is a rate performance diagram of a symmetrical battery assembled with a zinc negative electrode having an MCM-41 protective layer prepared in an embodiment of the present invention and a symmetrical battery assembled with an unmodified bare zinc negative electrode in a comparative example;
[0020] Figure 5 The Tafel curves of the symmetrical battery assembled with the zinc negative electrode having the MCM-41 protective layer prepared in the embodiment of the present invention and the symmetrical battery assembled with the unmodified bare zinc negative electrode in the comparative example;
[0021] Figure 6 XRD diagrams of the zinc negative electrode with MCM-41 protective layer prepared in the embodiment of the present invention and the unmodified bare zinc negative electrode in the comparative example after 200 cycles of constant current cycling;
[0022] Figure 7 This is a SEM image of the zinc negative electrode with MCM-41 protective layer prepared in the embodiment of the present invention and the unmodified bare zinc negative electrode in the comparative example after 200 cycles of constant current cycling;
[0023] Figure 8 This is a SEM image of the cross section of a zinc negative electrode with an MCM-41 protective layer prepared in an example of the present invention. DETAILED DESCRIPTION
[0024] The embodiments described are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example:
[0026] The preparation method of the zinc negative electrode with the MCM-41 protective layer comprises the following steps:
[0027] 1) 200 mL of deionized water, 4 mL of 1 M sodium hydroxide solution and 1.04 g of hexadecyltrimethylammonium bromide were added to a three-necked flask, mechanically stirred at 80°C for 1.5 h to mix evenly, then 5 mL of tetraethyl orthosilicate was added, and stirring was continued for 2 h, and then aged in an air atmosphere for 15 h. After the reaction was completed, the mixture was filtered, washed repeatedly with deionized water and ethanol for 3 times, dried at 80°C for 48 h, and the product was placed in a muffle furnace and heated to 550°C at 2°C / min for 4 h to obtain MCM-41 powder;
[0028] 2) Grind 0.18 g of MCM-41 powder and 0.02 g of polyvinylidene fluoride for 30 min to mix evenly, put them into a weighing bottle, add N-methylpyrrolidone solvent to make a slurry, and evenly apply the obtained slurry on the surface of zinc foil with a scraper. After vacuum drying, cut into discs with a diameter of 14 mm to obtain a zinc negative electrode with an MCM-41 protective layer.
[0029] The zinc foil in the embodiment is pretreated before use: the pretreatment is to grind the zinc foil with sandpaper to remove the oxide film, put it in an ethanol solution for ultrasonic treatment for 30 minutes and then dry it. Figure 8 It can be seen that in the cross section of the zinc negative electrode with the MCM-41 protective layer prepared in the example, the MCM-41 protective layer is evenly distributed and the thickness of the MCM-41 protective layer is 20 μm.
[0030] Comparative Example:
[0031] The zinc foil was sanded to remove the oxide film, placed in an ethanol solution for 30 minutes of ultrasonic treatment and then dried, and cut into discs with a diameter of 14 mm to obtain an unmodified bare zinc negative electrode. No other treatment was performed.
[0032] The XRD patterns of the zinc negative electrode with MCM-41 protective layer prepared in the embodiment and the unmodified bare zinc negative electrode in the comparative example obtained by X-ray diffractometer are as follows: Figure 1 shown by Figure 1 It can be seen that compared with the zinc standard PDF card, a broad peak of MCM41 is shown at 22° without any impurity peak, which proves that the MCM-41 protective layer is successfully coated on the zinc foil surface in the embodiment.
[0033] The SEM images of the zinc negative electrode surface with MCM-41 protective layer obtained in the embodiment and the unmodified bare zinc negative electrode surface in the comparative example are as follows: Figure 2 shown by Figure 2 It can be seen that the MCM41 protective layer on the surface of the zinc negative electrode with the MCM-41 protective layer prepared in the example is smooth and dense, and the pores are evenly distributed.
[0034] The zinc negative electrode with MCM-41 protective layer prepared in the example and the unmodified bare zinc negative electrode in the comparative example were respectively assembled into CR2032 type Zn-Zn symmetrical batteries, 2M ZnSO4 aqueous solution was used as electrolyte, glass fiber was used as separator, constant current charge and discharge tests were carried out on the Xinwei battery test system, and Tafel curves were tested and analyzed on the electrochemical workstation.
[0035] At a current density of 1 mA cm -2 , surface capacity 1mAh cm -2The constant current charge and discharge test was carried out under the condition of 400 ℃ and 800 ℃, and the cycle performance comparison of the symmetrical battery assembled by the zinc negative electrode with MCM-41 protective layer prepared in the embodiment and the unmodified bare zinc negative electrode in the comparative example was obtained as shown in the figure. Figure 3 shown by Figure 3 It can be seen that compared with the unmodified bare zinc negative electrode in the comparative example, the zinc negative electrode with the MCM-41 protective layer prepared in the embodiment shows better cycle stability. The zinc negative electrode with the MCM-41 protective layer prepared in the embodiment can effectively improve the cycle performance of the battery.
[0036] Surface capacity 1 mAh cm -2 The rate performance test was carried out under the following conditions, and the current density during the cycle was changed to obtain a rate performance comparison diagram of a symmetrical battery assembled with the zinc negative electrode with MCM-41 protective layer prepared in the embodiment and the unmodified bare zinc negative electrode in the comparative example. Figure 4 shown by Figure 4 It can be seen that compared with the unmodified bare zinc negative electrode in the comparative example, the zinc negative electrode with an MCM-41 protective layer prepared in the embodiment shows a stable deposition-stripping process at different current densities, indicating that the zinc negative electrode with an MCM-41 protective layer prepared in the embodiment has good rate performance.
[0037] The Tafel curves of the batteries assembled from the zinc negative electrode with the MCM-41 protective layer prepared in the embodiment and the unmodified bare zinc negative electrode in the comparative example are shown in FIG. Figure 5 shown by Figure 5 It can be seen that the corrosion potential of the prepared zinc negative electrode with MCM-41 protective layer is more positive than that of the unmodified bare zinc negative electrode in the comparative example, and the tendency of corrosion reaction is smaller; the corrosion current of the prepared zinc negative electrode with MCM-41 protective layer is smaller than that of the unmodified bare zinc negative electrode in the comparative example, indicating that the zinc negative electrode with MCM-41 protective layer prepared in the embodiment has better corrosion resistance.
[0038] The XRD patterns of the zinc negative electrode with MCM-41 protective layer prepared in the embodiment and the unmodified bare zinc negative electrode in the comparative example after 200 cycles of constant current cycling are shown in the figure: Figure 6 shown by Figure 6 It can be seen that the unmodified bare zinc negative electrode in the comparative example clearly shows the characteristic peaks of by-products. On the contrary, the peak of the zinc negative electrode with the MCM-41 protective layer prepared in the embodiment is effectively suppressed, which indicates that the corrosion of the zinc negative electrode is improved and the MCM41 protective layer has excellent corrosion resistance and outstanding stability.
[0039] The SEM images of the zinc negative electrode surface with MCM-41 protective layer obtained in the embodiment and the unmodified bare zinc negative electrode surface in the comparative example after 200 cycles of constant current cycling are as follows: Figure 7shown by Figure 7 It can be seen that the zinc coating on the unmodified bare zinc negative electrode in the comparative example presents an irregular random morphology, and many protrusions and by-products appear on the surface. On the contrary, the MCM-41 protective layer on the surface of the zinc negative electrode with the MCM-41 protective layer prepared in the embodiment remains uniform and the morphology remains unchanged. It can be seen that the MCM-41 protective layer can effectively induce uniform zinc deposition and prevent the generation of zinc by-products to a certain extent, thereby improving the cycle stability of the zinc negative electrode.
[0040] In summary, the zinc negative electrode with MCM-41 protective layer prepared in the embodiment of the present invention shows better cycle stability than the unmodified bare zinc negative electrode in the comparative example; the symmetrical battery assembled with the zinc negative electrode with MCM-41 protective layer prepared in the embodiment shows better rate performance than the symmetrical battery assembled with the unmodified bare zinc negative electrode in the comparative example; after 200 cycles, there are a large number of zinc dendrites on the surface of the unmodified bare zinc negative electrode in the comparative example, while there is no dendrite generation on the surface of the zinc negative electrode electrode with MCM-41 protective layer in the embodiment, which realizes uniform and stable deposition of zinc ions and can effectively inhibit zinc dendrites. The MCM-41 protective layer prepared in the present invention can uniformly distribute ion flux and realize dendrite-free deposition; at the same time, the protective layer acts as a physical barrier to effectively block the zinc negative electrode from direct contact with water molecules in the electrolyte, inhibiting side reactions such as dendrites and corrosion, and the method provided by the present invention has simple reaction conditions, easy operation and control, low cost, and can realize large-scale production.
[0041] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a zinc negative electrode having an MCM-41 protective layer, characterized in that: The steps include: 1) Hexadecyltrimethylammonium bromide, sodium hydroxide and deionized water were heated and stirred for 1.5 hours, and then ethyl orthosilicate was added and heated and stirred for 2 hours to obtain a mixed solution. The obtained mixed solution was aged in an air atmosphere for 15 hours, centrifuged and washed, and then dried and placed in a porcelain boat, and the temperature was uniformly raised to 550° C. and calcined for 4 hours, and then naturally cooled to obtain MCM-41 powder; 2) The obtained MCM-41 powder and polyvinylidene fluoride were ground and mixed in a mass ratio of 9:1, N-methylpyrrolidone was added dropwise and magnetic stirring was performed for 4 hours to prepare a slurry, and the obtained slurry was evenly scraped on the surface of the zinc metal negative electrode with a scraper, and the zinc negative electrode with an MCM-41 protective layer was obtained after vacuum drying.
2. The method for preparing a zinc negative electrode having an MCM-41 protective layer according to claim 1, characterized in that: In the step 1), the mass ratio of hexadecyltrimethylammonium bromide, sodium hydroxide, deionized water and tetraethyl orthosilicate is 1:0.15:192.31:4.
81.
3. The method for preparing a zinc negative electrode having an MCM-41 protective layer according to claim 1, characterized in that: The stirring temperature in step 1) is 40-80°C.
4. The method for preparing a zinc negative electrode having an MCM-41 protective layer according to claim 1, characterized in that: In the step 1), the aging temperature is 40-80° C. and the aging time is 10-15 hours.
5. The method for preparing a zinc negative electrode having an MCM-41 protective layer according to claim 1, characterized in that: The detergent used for washing in step 1) is deionized water or anhydrous ethanol, the drying temperature is 40-80° C., and the drying time is 48 hours.
6. The method for preparing a zinc negative electrode having an MCM-41 protective layer according to claim 1, characterized in that: The calcination heating rate in step 1) is 1-2°C / min.
7. The method for preparing a zinc negative electrode having an MCM-41 protective layer according to claim 1, characterized in that: In the step 2), the vacuum drying temperature is 40-80° C. and the vacuum drying time is 10-15 hours.
8. The modified zinc negative electrode obtained by the preparation method of the zinc negative electrode with MCM-41 protective layer according to any one of claims 1 to 7.
9. Use of the modified zinc negative electrode obtained by the preparation method of the zinc negative electrode with MCM-41 protective layer as claimed in claim 8 in an aqueous zinc ion battery.
Citation Information
Patent Citations
Surface-modified ordered mesoporous silicon dioxide composite material and its preparation method
CN102476803A
Cerium-niobium-antimony-based composite particle photocatalyst of porous nano-structure and preparation and application thereof
CN104525182A
Preparation method of carbon molecular sieve-cobalt monatomic catalyst for zinc air battery
CN114284512A
Porous material
JP2004249407A
Cited By
Aqueous zinc ion battery and preparation and application of modified zinc negative electrode of aqueous zinc ion battery
CN119833526A
Preparation and application of aqueous zinc-ion battery and modified zinc anode thereof
CN119833526B
